2018
DOI: 10.1186/s12959-018-0188-y
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban versus standard anticoagulation for acute venous thromboembolism in childhood. Design of the EINSTEIN-Jr phase III study

Abstract: BackgroundVenous thromboembolism (VTE) is a relatively rare condition in childhood with treatment mainly based on extrapolation from studies in adults. Therefore, clinical trials of anticoagulation in children require novel approaches to deal with numerous challenges. The EINSTEIN-Jr program identified pediatric rivaroxaban regimens commencing with in vitro dose finding studies followed by evaluation of children of different ages through phase I and II studies using extensive modeling to determine bodyweight-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…EINSTEIN-Jr. (clinicaltrials.gov: NCT02234843) is a randomized, open-label, multicenter trial that compared the efficacy and safety of rivaroxaban with those of standard anticoagulants for treatment of VTE and evaluated the PK of rivaroxaban. 15 Clinical efficacy and safety results have previously been published. 6 The study was conducted at 107 sites in Australia, Europe, Israel, Japan, China, South America, and North America.…”
Section: Methodsmentioning
confidence: 99%
“…EINSTEIN-Jr. (clinicaltrials.gov: NCT02234843) is a randomized, open-label, multicenter trial that compared the efficacy and safety of rivaroxaban with those of standard anticoagulants for treatment of VTE and evaluated the PK of rivaroxaban. 15 Clinical efficacy and safety results have previously been published. 6 The study was conducted at 107 sites in Australia, Europe, Israel, Japan, China, South America, and North America.…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol, the clinical efficacy and safety results, and the rivaroxaban dose-exposure response have been published. 19,20,25 The statistical analysis plan for this prespecified substudy can be found in the supplemental Data. The institutional review board at each participating center approved the study protocol.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…19 The absolute incidences of study outcomes and relative treatment effects observed with rivaroxaban were similar to those in the large rivaroxaban VTE studies in adults. 19,[23][24][25] We present a predefined subgroup analysis of the safety and efficacy of rivaroxaban and standard anticoagulants in the 114 children who presented with CVT in the EINSTEIN-Jr phase 3 trial. 19…”
Section: Introductionmentioning
confidence: 99%
“…Presently, several direct oral anticoagulants (DOACs) are undergoing evaluation in paediatric development programs [ 68 , 69 , 70 , 71 , 72 , 73 ]. Randomized clinical trials for DOACs in paediatric VTE are ongoing.…”
Section: Treatmentmentioning
confidence: 99%